Mixed convection of non-newtonian erying powell fluid with temperature-dependent viscosity over a vertically stretched surface - Aljabali, Ahlam; Abdul Rahman, Mohd Kasim; Nur Syamilah, Arifin; Sharena, Mohamad Isa (Tech Science Press, 2021)
The viscosity of a substance or material is intensely influenced by the temperature, especially in the field of lubricant engineering where the changeable temperature is well executed. In this paper, the problem of temperature-dependent viscosity on mixed convection flow of Eyring Powell fluid was studied together with Newtonian heating thermal boundary condition. The flow was assumed to move over a vertical stretching sheet. The model of the problem, which is in partial differential equations, was first transformed to ordinary differential equations using appropriate transformations. This approach was considered to reduce the complexity of the equations. Then, the transformed equations were solved using the Keller box method under the finite difference scheme approach. The validation process of the results was performed, and it was found to be in an excellent agreement. The results on the present computation are shown in tabular form and also graphical illustration. The major finding was observed where the skin friction and Nusselt number were boosted in the strong viscosity.